1998
DOI: 10.1074/jbc.273.48.32187
|View full text |Cite
|
Sign up to set email alerts
|

The Topology of the Substrate Binding Clefts of Glycosyl Hydrolase Family 10 Xylanases Are Not Conserved

Abstract: The crystal structures of family 10 xylanases indicate that the distal regions of their active sites are quite different, suggesting that the topology of the substrate binding clefts of these enzymes may vary. To test this hypothesis, we have investigated the rate and pattern of xylooligosaccharide cleavage by the family 10 enzymes, Pseudomonas fluorescens subsp. cellulosa xylanase A (XYLA) and Cellulomonas fimi exoglucanase, Cex. The data showed that Cex contained three glycone and two aglycone binding sites,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
115
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(123 citation statements)
references
References 25 publications
6
115
0
2
Order By: Relevance
“…The crystal structures of xylanases show that GH10 enzymes fold into a (␤/␣) 8 -barrel (6, 7), whereas family 11 enzymes are ␤-jelly roll proteins (8). Consistent with their "endo" mode of action, the substrate binding cleft of xylanases extends along the length of the proteins and can accommodate from four to seven xylose residues (9,10). Each region that accommodates xylose moieties are known as subsites, which are given a negative or positive number dependent on whether they bind the glycone or aglycone region of the substrate, respectively, with glycosidic bond cleavage occurring between the Ϫ1 and ϩ1 subsites (11).…”
mentioning
confidence: 86%
“…The crystal structures of xylanases show that GH10 enzymes fold into a (␤/␣) 8 -barrel (6, 7), whereas family 11 enzymes are ␤-jelly roll proteins (8). Consistent with their "endo" mode of action, the substrate binding cleft of xylanases extends along the length of the proteins and can accommodate from four to seven xylose residues (9,10). Each region that accommodates xylose moieties are known as subsites, which are given a negative or positive number dependent on whether they bind the glycone or aglycone region of the substrate, respectively, with glycosidic bond cleavage occurring between the Ϫ1 and ϩ1 subsites (11).…”
mentioning
confidence: 86%
“…19) Kaneko et al reported that Arg237 of CF forms a hydrogen bond to the xylose at subsite þ2, and that the contribution of Phe286 and Tyr171 to binding explains the high binding energy at the þ2 subsite. 45) Although tyrosine residue was found to be conserved in all four of the enzymes used in this study, the arginine and phenylalanine residues were conserved only in TM and CF, not in CS or BH, as determined by amino acid sequence alignment analysis using ClustalW 47) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The topological variety of the +subsites appears to be responsible for the substrate specificity of these enzymes. 19) Glycosynthases are mutant enzymes derived from retaining glycoside hydrolases by substituting the catalytic nucleophilic residue into a non-nucleophilic amino acid residue. These enzymes catalyze the inverting glycosyl transfer reaction from glycosyl fluoride of the opposite anomer as a donor substrate and an acceptor molecule.…”
mentioning
confidence: 99%
“…24,25) To examine the function of XBM in the xylan hydrolysis, an XBM deleted enzyme consisting of residues 1 to 303 and the full length enzyme consisting of residues 1 to 436 were used. Reaction mixtures containing 150 µL of McIlvaine buffer, 50 µL of 1% (w v) BSA and 250 µL of insoluble oat spelts xylan solution (2 mg mL) were equilibrated at 30 C for 5 min, and then reactions were initiated by the addition of 50 µL of enzyme solution (0.05 mg mL).…”
Section: Methodsmentioning
confidence: 99%